Feasibility and preliminary effectiveness of a highly intensive inpatient treatment programme with Narrative Exposure Therapy for patients with posttraumatic stress disorder - Strijk, Patricia J. M.; Nijdam, Mirjam J.; Klaassens, Ellen R.; Bedawi, Viyan; de la Rie, Simone; Jongedijk, Ruud A. (Frontiers in Psychology, 2025)
IntroductionCurrent guidelines recommend trauma-focused therapies for the treatment of post-traumatic stress disorder (PTSD). Unfortunately, the percentage of non-response and dropout with these forms of therapy has proven to be substantial. Trauma-focused therapies offered in a highly intensive format have been found to lead to higher adherence and faster symptom reduction, but no studies so far have investigated Narrative Exposure Therapy (NET) in an intensive programme. The aim of this study was to investigate the feasibility and preliminary effects of a 10-day highly intensive inpatient treatment programme consisting of Narrative Exposure Therapy (NET), Art Therapy (AT) and trauma sensitive yoga (TSY) for patients with severe, chronic PTSD.MethodsA non-controlled pilot study was conducted in which 28 individuals diagnosed with PTSD received this highly intensive treatment programme. Outcome measures were administered at baseline, post-treatment and at four-month follow-up. Changes in clinician-rated and self-reported PTSD were explored, as well as changes in depressive symptoms and general psychopathology. Outcome measures were the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5), PTSD Check List for DSM-5 (PCL-5), Beck Depression Inventory (BDI-II), and Brief Symptom Inventory (BSI).ResultsFrom baseline to four-month follow-up, clinician-rated and self-reported PTSD symptom severity significantly decreased with a large effect size (Cohen’s d 0.80 and 0.84, respectively). Depressive symptom severity showed a medium-sized decrease at post-treatment, which was enhanced at four-month follow-up representing a large effect (Cohen’s d 0.78). The drop-out rate was 18%.ConclusionThe findings of this study show that applying NET in a highly intensive form is feasible and significant improvements in PTSD and depressive symptoms were demonstrated in patients who had all received previous treatment for their condition. Future research into this promising approach is encouraged, as well as investigating which patients benefit most from highly intensive programs with NET.